2021
DOI: 10.3892/ijmm.2021.5029
|View full text |Cite
|
Sign up to set email alerts
|

Calcium chelator BAPTA‑AM protects against iron overload‑induced chondrocyte mitochondrial dysfunction and cartilage degeneration

Abstract: Osteoarthritis (OA) is a common joint disease that is characterized by cartilage degradation. Iron deposition in the joints is common during the pathogenic progression of OA and recent studies have indicated that iron overload is an important contributor to OA progression. calcium chelators have been reported to inhibit iron influx via modulating transferrin receptor protein 1 internalization, and they have been identified as a potential approach to the treatment of iron overload-induced diseases. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…The iron chelator DFO [ 9 , 57 , 60 , 83 , 88 , 116 ] and the antioxidants Fer-1 [ 8 , 9 , 71 , 82 , 83 , 117 ] and CoQ10 [ 119 , 120 ] have shown significant anti-OA effects both in vitro and in vivo. This anti-OA effect has also been demonstrated in vitro by the calcium chelator BAPTA acetoxymethyl ester [ 86 ], the natural iron chelator lactoferrin [ 89 ], and the antioxidants NAC [ 101 , 116 ] and vitamin E [ 109 ]. An increasing number of agents, such as platelet-rich plasma [ 78 ], nifedipine [ 94 ], and icariin [ 97 ], have also been studied.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The iron chelator DFO [ 9 , 57 , 60 , 83 , 88 , 116 ] and the antioxidants Fer-1 [ 8 , 9 , 71 , 82 , 83 , 117 ] and CoQ10 [ 119 , 120 ] have shown significant anti-OA effects both in vitro and in vivo. This anti-OA effect has also been demonstrated in vitro by the calcium chelator BAPTA acetoxymethyl ester [ 86 ], the natural iron chelator lactoferrin [ 89 ], and the antioxidants NAC [ 101 , 116 ] and vitamin E [ 109 ]. An increasing number of agents, such as platelet-rich plasma [ 78 ], nifedipine [ 94 ], and icariin [ 97 ], have also been studied.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, high doses of FAC increased labile iron and ROS levels, decreased COL2 production, disrupted the cell cycle, and increased the cell death rate compared with untreated controls. Jing et al [ 86 ] found increased intracellular iron and ROS levels and higher expression of MMP-3, MMP-13, and ADAMTS-5 in FAC-treated chondrocytes. Moreover, they detected mitochondrial dysfunction.…”
Section: Potential Association Between Ferroptosis and Oa: Cell Researchmentioning
confidence: 99%
“…Jing et al reported that the calcium chelator BAPTA-AM could decrease the extent of iron influx realized into chondrocytes. This helped inhibit iron overload-stimulated ROS accumulation and mitochondrial dysfunction (Jing et al, 2021b). In addition, D-mannose exerted a chondroprotective effect by attenuating the sensitivity of chondrocytes toward ferroptosis and alleviating OA progression.…”
Section: Therapeutic Strategymentioning
confidence: 98%
“…Based on the theory that iron overload promotes OA by inducing ROS production and mitochondrial dysfunction, Han et al further revealed that the calcium chelator, BAPTA-AM, suppressed the influx of iron into chondrocytes and effectively restrained iron overload-mediated ROS accumulation and mitochondrial dysfunction. This suggested that calcium chelators played important roles during the treatment of iron metabolism-related OA (Jing et al, 2021b).…”
Section: Effects Of Iron Overload On Chondrocyte Dysfunction and Cart...mentioning
confidence: 99%
“…Excess iron causes an increased production of reactive oxygen species leading to cell dysfunction or death, tissue damage and organ disease [ 9 ]. Iron overload has been shown to promote apoptosis of osteoblasts, chondrocytes, cardiomyocytes and liver cells by inducing endoplasmic reticulum (ER) stress or mitochondrial dysfunction [ [10] , [11] , [12] ]. However, the effect of iron overload on peripheral nerves is rarely studied.…”
Section: Introductionmentioning
confidence: 99%